C57BL/6N albino/agouti mutant mice as embryo donors for efficient germline transmission of C57BL/6 ES cells. - Branko Zevnik; Nathalie C Uyttersprot; Ana V Perez; Gerald W M Bothe; Heidrun Kern; Gunther Kauselmann (PLoS ONE)
We generated C57BL/6NTac mice carrying a tyrosinase loss-of function mutation and a reversion of the nonagouti locus to agouti. This strain has a high superovulation response, allows visual detection of chimeric coat color contribution of C57BL/6 ES-cells and provides a simplified breeding format that generates black G1 offspring of pure inbred C57BL/6 background in one step, providing the ideal host for genetically manipulated C57BL/6 ES cells.